Nutritional evaluation of the legume Macrotyloma axillare using in vitro and in vivo bioassays in sheep. Issue 2 (10th October 2017) - Lima, P. M. T.; Moreira, G. D.; Sakita, G. Z.; Natel, A. S.; Mattos, W. T.; Gimenes, F. M. A.; Gerdes, L.; McManus, C.; Abdalla, A. L.; Louvandini, H.
Summary: This study consisted of two experiments with the following objectives: to evaluate the effects of tannins from the tropical legume macrotiloma ( Macrotyloma axillare ) on total gas and methane (CH4 ) production, as well as on ruminal fermentation parameters by performing an in vitro bioassay, with samples incubated with and without polyethylene glycol (PEG) in a semi‐automatic system; and secondly in a 17 day in vivo experiment, to determine apparent total tract digestibility (ATTD) of dietary nutrients and ruminal fermentation parameters of 12 intact 8‐ to 9‐month‐old Santa Inês (averaging 24.95 ± 1.8 kg body weight) ewes fed tropical grass hay supplemented with macrotiloma hay. The ewes were divided into two treatment groups depending on their diet: chopped aruana grass hay ( Panicum maximum cv. Aruana) (control—CON); and aruana grass hay supplemented with chopped macrotiloma hay (macrotiloma—MAC). The animals were kept for 5 consecutive days in metabolic cages for the ATTD assay, and at the end of this period, samples of rumen fluid were collected from each ewe to determine ammoniacal nitrogen (NH3 ‐N) and short‐chain fatty acid (SCFA) production, and protozoa count. For the in vitro assay, a decrease in total gas and CH4 production was observed for samples incubated without PEG ( p  <   .05). No differences were observed for the other parameters evaluated ( p  >   .05). In the in vivo experiment, increased intake and ATTD of crude protein were observed for the animals fed MAC when compared to CON ( p  <   .05). For rumen fermentation parameters, increased NH3 ‐N, total SCFA and iso butyrate concentrations, as well as reduced protozoa count were observed for MAC when compared to CON ( p  <   .05). The results observed here indicated the potential of macrotiloma for use as a ruminant feed, and antimethanogenic potential of this plant was noted.